Application of Autologous Peripheral Blood Mononuclear Cells into the Area of Spinal Cord Injury in a Subacute Period: A Feasibility Study in Pigs - Iliya Shulman; Sergei Ogurcov; Alexander Kostennikov; Alexander Rogozin; Ekaterina Garanina; Galina Masgutova; Mikhail Sergeev; Albert Rizvanov; Yana Mukhamedshina (Biology, 2021)
Peripheral blood presents an available source of cells for both fundamental research and clinical use. In our study, we have evaluated the therapeutic potential of peripheral blood mononuclear cells (PBMCs) excluding the preliminary sorting or mobilization of peripheral blood stem cells. We have evaluated the regenerative potential of PBMCs embedded into a fibrin matrix (FM) in a model of pig spinal cord injury. The distribution of transplanted PBMCs in the injured spinal cord was evaluated; PBMCs were shown to penetrate into the deep layers of the spinal cord and concentrate mainly in the grey matter. The results of the current study revealed an increase in the tissue integrity in the area adjacent to the epicenter of injury and the partially restored conduction along posterior columns of the spinal cord in animals after FM+PBMC application. The multiplex analysis of blood serum and cerebrospinal fluid showed the cytokine imbalance to occur without significantly shifting toward pro-inflammatory or anti-inflammatory cytokine cascades.